Hydrological proceses, chemical variability, and multiple isotopestracing of water flow paths in the Kudumela Wetland- Limpopo Province, South Africa - Mekiso, Feleke Abiyo (Rhodes University, Faculty of Science, Institute for Water Research, 2011)
The hydrology of the Kudumela Wetland, Limpopo Province of South Africa was studied from November 2005 to April 2007, involving both fieldwork and laboratory analyses. This study presents the results of an investigation of the hydrology of the Kudumela Wetland in South Africa, and its contribution to dry season flow in the Mohlapitsi and Olifants Rivers. Initially, 40 Piezometers were installed along seven transects and water levels monitored in order to understand water table level characteristics (fluctuations) with time. Water levels in transects one, three, the right bank portion of transect four and transect six showed fluctuations. Transect two, the left bank portion of transect four and transect five did not show significant temporal changes. The relationships between piezometer water levels, rainfall in the study area and stream flow observed at a river gauging station are not clear. The river within the wetland is a gaining stream because the water table level elevation is above that of the river. This indicates that the wetland is feeding the river. The northern part of the wetland (T1 and T2) is affected by artificial drains and most of the piezometers closest to the river channel showed the lowest variations. The relationships between rainfall, groundwater, and surface water at this site shows that stream flow did not respond quickly to precipitation as expected, even in months when rainfall increased (for example, 74 and 103mm during 08/02/06 and 18/02/06 respectively), and the groundwater levels did not show fluctuations, indicating that groundwater responds gradually to precipitation, and that the relationship between rainfall, groundwater and surface water is complex. The environmental stable isotopes (deuterium and oxygen-18) and the radioactive isotope (tritium) were analyzed, along with field observations of electrical conductivity (EC), pH, total alkalinity (Talka) and some major and minor dissolved ion analyses for tracing water dynamics in the study area. A total of 39 water samples was taken and analyzed from boreholes, auger holes, right bank and left bank drains, various points along the river and springs in four sampling visits to the wetland. The results did not clearly provide a temporal record of isotope and chemical variations in the various sources. Results from the most extensive sampling survey in April 2007 provide the most comprehensive overview of hydrological relationships. Clustering of the stable isotope data suggests that the water samples of upstream and downstream river, auger holes further south and most drains clustered together suggesting a common water source and almost all samples fall above the global (GMWL) and local (Pretoria MWL) meteoric water lines, while some fall between the global and Pretoria meteoric water lines. Six representative water samples were analyzed for major ion concentration. Both cation (Ca, Mg, K, and Na) and anion (HCO3, SO4, Cl, and NO3) analyses in November 2007 confirmed conclusions reached from field observations. The analysis shows that a single type of water (Ca, Mg-HCO3) is involved in the study area. In almost all major ion plots, the right bank drains, upstream river and downstream river samples grouped together in a single cluster. As the means for reliable river flow measurements were not available, except for the gauging station at the outlet of the valley, rough, semi-quantitative estimates were made during several field visits. These, suggest considerable losses of river flow into the gravel/boulder beds at and below a gabion dam at the head of the valley. Three major and several other left bank springs and right bank drains at transects T1 and T2 contributed to the river flow at all times. Along with the isotopic and chemical evidence, these observations have lead to a hypothesis that river water enters the wetland and flows back to the Mohlapitsi River through boulder beds underlying the wetland and through drains on the surface of the argillaceous aquitard covering the more conductive boulder beds. Deeper dolomitic groundwater does not appear to contribute to the water balance at least in the northern half of the wetland. Although environmental isotope and hydrochemistry results may not unequivocally prove this hypothesis they do not contradict it.
Keywords: Kudumela Wetland -- South Africa -- Limpopo; Wetland hydrology -- South Africa -- Limpopo; Wetlands -- South Africa -- Limpopo; Wetland conservation -- South Africa -- Limpopo; Wetland management -- South Africa -- Limpopo; Isotopes